Morphometric Analysis of Foramen Magnum in Adult Human Skulls Using 3D CT Imaging - Rashid, Mohammed Enamur (Bangladesh Journal of Medical Science, 2026)
Background The foramen magnum (FM) is a crucial anatomical landmark at the craniovertebral junction. Its morphometric parameters are of paramount importance in various clinical disciplines, including neurosurgery, radiology, and forensic anthropology. While traditional osteometric studies exist, modern imaging techniques like 3D computed tomography (CT) offer a more precise and non-invasive method for in vivo analysis. Methods A retrospective cross-sectional study was conducted on 200 head CT scans (100 males, 100 females) of adults aged 18-70 years. Multiplanar reconstructions and 3D volumerendered images were generated. Key parameters, including anteroposterior (AP) diameter, transverse (TR) diameter, and area, were measured using standardized anatomical landmarks. Statistical analysis was performed to compare the parameters between genders. Results The mean AP diameter was 35.8 ± 2.1 mm in males and 32.4 ± 1.9 mm in females (p < 0.001). The mean TR diameter was 30.5 ± 1.8 mm in males and 27.9 ± 1.7 mm in females (p < 0.001). The mean calculated area was 860.4 ± 85.2 mm² in males and 712.3 ± 78.6 mm² in females (p < 0.001). All measured parameters were significantly larger in males than in females. The Foramen Magnum Index (FMI) did not show a statistically significant difference between the sexes. Conclusion The study provides reliable normative morphometric data for the foramen magnum in the studied population using 3D CT imaging. The significant sexual dimorphism observed in all linear and area measurements highlights the necessity of sex-specific reference standards. These findings have direct clinical applications in neurosurgical planning, radiological diagnosis of pathologies at the craniovertebral junction, and forensic identification. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S119-S123